2001
DOI: 10.1038/sj.ejhg.5200712
|View full text |Cite
|
Sign up to set email alerts
|

An mtDNA mutation, 14453G→A, in the NADH dehydrogenase subunit 6 associated with severe MELAS syndrome

Abstract: We report a novel point mutation in the gene for the mitochondrially encoded ND6 subunit of the NADH:ubiquinone oxidoreductase (complex I of the respiratory chain) in a patient with MELAS syndrome. The mutation causes a change from alanine to valine in the most conserved region of the ND6 subunit. The patient was heteroplasmic for the mutation in both muscle and blood, but the mutation was not detected in the patient's mother. A marked reduction of complex I activity was found in the patient's muscular tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…[28][29][30][31] In this study, we found T10191C in MTND3, and a large deletion (from 13025-13033/to 14417-14425/) encompassing partial MTND5 and MTND6 in patients 2 and 3, respectively. The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation.…”
Section: Discussionmentioning
confidence: 66%
“…[28][29][30][31] In this study, we found T10191C in MTND3, and a large deletion (from 13025-13033/to 14417-14425/) encompassing partial MTND5 and MTND6 in patients 2 and 3, respectively. The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation.…”
Section: Discussionmentioning
confidence: 66%
“…17 This region harbors mutations previously associated with Leigh syndrome 19 and MELAS, 20 and it is a hot-spot for mutations leading to LHON or LHON/dystonia. 4 The LHON primary mutation T14484C causes the same amino acid substitution in the position adjacent to the M63V change.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the translational activity of ND6 in cybrid cells is specifically and markedly reduced without a decrease in total mitochondrial protein synthesis when the A3243G or T3271C mtDNA levels are increased (13,14). Furthermore, a point mutation (A14453G) in the structural gene for ND6 was found to be associated with severe MELAS syndrome (47).…”
Section: Discussionmentioning
confidence: 99%